2019
DOI: 10.3390/coatings9100647
|View full text |Cite
|
Sign up to set email alerts
|

Impact of K+ Doping on Modulating Majority Charge Carrier Type and Quality of Perovskite Thin Films by Two-step Solution Method for Solar Cells

Abstract: Traditional hetero-junction perovskite solar cells are composed of light-absorbing layers, charge carrier-transporting layers, and electrodes. Recently, a few papers on homo-junction perovskite solar cells have been studied. Here, we studied the effect of K+ doping on TiO2/PbI2 interface quality, perovskite film morphology, photo-physical properties, and majority carrier type. In particular, the K+ extrinsic doping can modulate the majority carrier type of the perovskite thin film. The study indicated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The modulation of majority charge carriers type and concentrations plays an important role in homo-junction PSCs. In the past research, the type of majority charge carriers was changed mainly through doping [20][21][22][23][24][25]. Huang et al [21] found that by changing the ratio of the two perovskite precursor solutions, CH 3 NH 3 PbI 3 can be adjusted to N-type or P-type by self-doping.…”
Section: Introductionmentioning
confidence: 99%
“…The modulation of majority charge carriers type and concentrations plays an important role in homo-junction PSCs. In the past research, the type of majority charge carriers was changed mainly through doping [20][21][22][23][24][25]. Huang et al [21] found that by changing the ratio of the two perovskite precursor solutions, CH 3 NH 3 PbI 3 can be adjusted to N-type or P-type by self-doping.…”
Section: Introductionmentioning
confidence: 99%